2008
DOI: 10.1179/174328407x185893
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sputtering power on mechanical properties of Cr films deposited by magnetron sputtering

Abstract: Chromium (Cr) films were deposited on plain carbon steel sheets by dc and rf magnetron sputtering as well as by electroplating. Effects of dc or rf sputtering power on the deposition rate and properties such as, hardness, adhesion strength, surface roughness and corrosion resistance of the Cr films were investigated. X-ray diffraction (XRD), atomic force microscopy (AFM), scanning electron microcopy (SEM) analyses were performed to investigate the crystal structure, surface roughness, thickness of the Cr films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…20,57,60) On the other hand, Cr is one of body-centered-cubic crystals, which often show á ñ 110 texture. 16,61,62) In spite of uncertain crystal directions and their volume ratios in the Cr layer, determined elastic constant of Cr is lower than bulk values 54) (a) (b) by 3%-14% as listed in Table II, which is similar with usual metal metallic thin films. From the above results, we conclude that thin metallic films show smaller elastic constants than those estimated from their bulk materials, and the GHz-RUS method is highly useful for measuring them correctly.…”
mentioning
confidence: 63%
“…20,57,60) On the other hand, Cr is one of body-centered-cubic crystals, which often show á ñ 110 texture. 16,61,62) In spite of uncertain crystal directions and their volume ratios in the Cr layer, determined elastic constant of Cr is lower than bulk values 54) (a) (b) by 3%-14% as listed in Table II, which is similar with usual metal metallic thin films. From the above results, we conclude that thin metallic films show smaller elastic constants than those estimated from their bulk materials, and the GHz-RUS method is highly useful for measuring them correctly.…”
mentioning
confidence: 63%
“…Hence, surface modification techniques can effectively overcome these problems and prolong its life span in a cavitation/corrosion environment. A lot of studies have been done to improve the wear and corrosion resistance of 304SS using surface modification techniques, such as magnetron sputtering technology [1], laser surface modification technique [2], plasma spraying [3] and arc-spraying [4] etc. Wang et al [5] synthesised amorphous or nanocrystalline CrNbTiMoZr high entropy alloy films on silicon wafers and 304 stainless steel by DC magnetron sputtering.…”
Section: Introductionmentioning
confidence: 99%
“…The fabrication of thin metallic films using magnetron sputtering has been investigated as a mean of controlling the surface nanoarchitecture of some solids (Cai et al , ; Wang et al , ). It has been shown that by altering sputtering conditions (e.g., power, Ar gas pressure), metallic films of differing roughness can be produced (Jeyachandran et al , ; Kim et al , ). Films of various thicknesses deposited in an identical way have also been shown to exhibit different roughness characteristics (Cai et al , ; Jeyachandran et al , ).…”
Section: Introductionmentioning
confidence: 99%